Formation of Systematic and Instrumental Competences of Future Geography Teachers in the Process of Using Electronic Information Media - Kovalchuk, Inna (My University, 2022)
The article is devoted to highlighting the possibilities of using electronic media in the formation of system and instrumental competencies of future geography teachers. The author draws attention to the advantages and disadvantages of using the Google calendar, the Moodle system, the corporate app, Vaber and Facebook, electronic manuals in the teaching of compulsory and optional subjects of the training plan of a specialist in distance learning. The introduction of electronic information media in distance education contributes to the implementation of the local studies principle in the teaching of geography; makes it possible to achieve accessibility, systematicity, scientificity, connection of learning with life. The practical implementation of the principle of student activity in learning will ensure the creation of a situation of success for future geography teachers, will promote emotionality in learning and the formation of positive motivation for professional activity.
Keywords: system and instrumental competences, information electronic media, future teachers of geography, educational program, teacher, criteria, indicators; electronic guide.